Lean library management : - Huber, John J. (Neal-Schuman Publishers, 2011)
Libraries today face reduced budgets, increased customer expectations, and aggressive competition from web-based information sources. In this book, author shows readers how to apply Lean principles and practices how making small, simple changes in everyday routines will reap large time- and money-saving results. Readers learn how to: create a culture of change, define and streamline library service delivery chains, transform everyday operations like placing customer reserves and technical service processes, implement performance measures that can drive continuous improvement, apply Lean techniques in digital operations